Exploring the multi-dimensional free energy surface of phosphoester hydrolysis with constrained QM/MM dynamics - Li, Wenjin; Gräter, Frauke (Journal of chemical theory and computation, 2012)
The mechanism of the hydrolysis of phosphate monoesters, a ubiquitous biological reaction, has remained under debate. We here investigated the hydrolysis of a nonenzymatic model system, the monomethyl phosphate dianion, by hybrid quantum mechanical and molecular mechanical simulations. The solvation effects were taken into account with explicit water. Detailed free energy landscapes in two-dimensional and three-dimensional space were resolved using the multidimensional potential of mean constraint force, a newly developed method that was demonstrated to be powerful for free energy calculations along multiple coordinates. As in previous theoretical studies, the associative and dissociative pathways were indistinguishable. Furthermore, the associative pathway was investigated in great detail. We propose a rotation of an O-H bond in the transition between two pentacoordinated structures, during which an overall transition state was identified with an activation energy of 50 kcal/mol. This is consistent with experimental data. The results support a concerted proton transfer from the nucleophilic water to the phosphate group, and then to the leaving group.